Impact of physical exercise on sensor performance of the FreeStyle Libre intermittently viewed continuous glucose monitoring system in people with Type 1 diabetes: a randomized crossover trial. Issue 5 (12th February 2019) - Moser, O.; Eckstein, M. L.; Mueller, A.; Birnbaumer, P.; Aberer, F.; Koehler, G.; Sourij, C.; Kojzar, H.; Holler, P.; Simi, H.; Pferschy, P.; Dietz, P.; et al.
Abstract: Aims: To evaluate the sensor performance of the FreeStyle Libre intermittently viewed continuous glucose monitoring system using reference blood glucose levels during moderate‐intensity exercise while on either full or reduced basal insulin dose in people with Type 1 diabetes. Methods: Ten participants with Type 1 diabetes [four women, mean ±sd age 31.4 ± 9.0 years, BMI 25.5±3.8 kg/m 2, HbA1c 55±7 mmol/mol (7.2±0.6%)] exercised on a cycle ergometer for 55 min at a moderate intensity for 5 consecutive days at the clinical research facility, while receiving either their usual or a 75% basal insulin dose. After a 4‐week washout period, participants performed the second exercise period having switched to the alternative basal insulin dose. During exercise, reference capillary blood glucose values were analysed using the fully enzymatic‐amperometric method and compared with the interstitial glucose values obtained. Intermittently viewed continuous glucose monitoring accuracy was analysed according to median (interquartile range) absolute relative difference, and Clarke error grid and Bland–Altman analysis for overall glucose levels during exercise, stratified by glycaemic range and basal insulin dosing scheme ( P <0.05). Results: A total of 845 glucose values were available during exercise to evaluate intermittently viewed continuous glucose monitoring sensor performance. The median (interquartile range) absolute relative difference between the reference values and those obtained by the sensor across the glycaemic range overall was 22 (13.9–29.7)%, and was 36.3 (24.2–45.2)% during hypoglycaemia, 22.8 (14.6–30.6)% during euglycaemia and 15.4 (9–21)% during hyperglycaemia. Usual basal insulin dose was associated with a worse sensor performance during exercise compared with the reduced (75%) basal insulin dose [median (interquartile range) absolute relative difference: 23.7 (17.2–30.7)% vs 20.5 (12–28.1)%; P <0.001). Conclusions: The intermittently viewed continuous glucose monitoring sensor showed diminished accuracy during exercise. Absolute glucose readings derived from the sensor should be used cautiously and need confirmation by additional finger‐prick blood glucose measurements. What's new?: The FreeStyle Libre (Abbott, Maidenhead, UK) intermittently viewed continuous glucose monitoring (iCGM) system is known to track changes in interstitial glucose with sufficient accuracy compared with blood glucose measurement in real‐life conditions. Our data revealed significant limitations in iCGM performance during physical exercise in people with Type 1 diabetes. The median (interquartile range) absolute relative difference overall was 22 (13.9–29.7)%, while during hypoglycaemia it was 36.3 (24.2–45.2)%, during euglycaemia it was 22.8 (14.6–30.6)% and during hyperglycaemia it was 15.4 (9–21)%. From a clinical point of view iCGM should only be used as an adjunct to blood glucose measurements to reduce the risk of glycaemic disturbances during physical exercise.